Impatiens galactica (Balsaminaceae), a new spurless species of section Trimorphopetalum from Madagascar - Fischer, Eberhard; Rahelivololona, Marie Elisette; Abrahamczyk, Stefan (Phytotaxa, 2017)
Impatiens galactica, a new species from lowland rainforest in Marojejy National Park, NE Madagascar, is described and illustrated. It belongs to Impatiens section Trimorphopetalum and is related to I. messmerae, also known from Mt. Marojejy. Impatiens galactica differs from the latter species in the shape of the lateral sepals, and in the dorsal petal and the lateral united petals being entirely glabrous and lacking small white scales. Furthermore, I. galactica has a distinct flower morphology with strongly reduced upper lobes of the lateral united petals. The lateral petals are thus resembling the lower case letter “b” or “d”, respectively. Additionally, it has unusually coloured yellowish white, semi-transparent flowers with an orange-yellow, shiny line along the midrib of the lower sepal, all of which are lacking in I. messmerae.